A Qualitative Analysis of Health Care Providers' Perceptions on Vitamin D Supplementation Program - Maryam Saberi-Karimian; Mina Minaei; Farzaneh Sadeghi; Morvarid Irani; Talaat Khadiv Zadeh; Ibrahim Elmadfa; Habibollah Esmaily; Hamideh Ghazizadeh; Payam Sharifan; Ameneh Timar; Zahra Abasalti; Mahdieh Sheikhi; et al. (Journal of Fasting and Health, 2022)
Previous studies have shown that the health burden associated with vitamin D deficiency is increasing globally. Vitamin D supplementation appears to be a feasible strategy for improving vitamin D status within populations. Little information is available on the perception and barriers to the widespread application of vitamin D supplements in Iran. Therefore, this study was conducted to explore the perception of health care providers regarding the implementation of vitamin D supplementation program in the Iranian cities of Mashhad, Qom and Zahedan.This qualitative conventional content analysis study was conducted at 3 medical universities in Iran: Mashhad (MUMS), Qom (QUMS) and Zahedan (ZAUMS) University of Medical Sciences. These universities, are within regions with differing prevalence of vitamin D deficiency, and were selected based on the results of National Integrated Micronutrient Survey 2012 (NIMS-II study). Individual semi-structured in-depth interviews were performed with 103 participants (consisting of health professionals and health providers) to understand the perceptions of health professionals and health care providers’. The data were collected from December 2018 to July 2019. Guba and Lincoln’s criteria were used to ensure the trustworthiness of the data. Data were analyzed using conventional content analysis based on the approach of Graneheim and Lundman's.There were three categories of barriers to distribution and use of individual supplements,  and the funding to implement the program; there were ten subcategories. Supplement distribution were affected by three subcategories of inadequate distribution of the supplement, irregular distribution of the supplement, and   insufficient space to store the supplements. Individual barriers to the use of supplement comprised five subcategories: forgetting to take them, lack of knowledge about their benefits, accessing a health care center providing them, negative advertising for supplement use, and not taking them because of cost. Funding to implement the program contained the two subcategories of financial limitation in urban and rural area and financial limitation for all target groups.The findings showed that health care providers reported a variety of barriers to supplement use. Applying a multiple strategy requires: training, conducting advertising campaigns, financial support, sufficient and regular distribution of the supplement and perhaps the use of alternative methods of supplement delivery, such as food fortification can be helpful.